Hydrogen Bonding Between Ions of Like Charge in Ionic Liquids Characterized by NMR Deuteron Quadrupole Coupling Constants—Comparison with Salt Bridges and Molecular Systems. (31st October 2019) - Khudozhitkov, Alexander E.; Neumann, Jan; Niemann, Thomas; Zaitsau, Dzmitry; Stange, Peter; Paschek, Dietmar; Stepanov, Alexander G.; Kolokolov, Daniil I.; Ludwig, Ralf
Abstract: We present deuteron quadrupole coupling constants (DQCC) for hydroxyl‐functionalized ionic liquids (ILs) in the crystalline or glassy states characterizing two types of hydrogen bonding: The regular Coulomb‐enhanced hydrogen bonds between cation and anion (c–a), and the unusual hydrogen bonds between cation and cation (c–c), which are present despite repulsive Coulomb forces. We measure these sensitive probes of hydrogen bonding by means of solid‐state NMR spectroscopy. The DQCCs of (c–a) ion pairs and (c–c) H‐bonds are compared to those of salt bridges in supramolecular complexes and those present in molecular liquids. At low temperatures, the (c–c) species successfully compete with the (c–a) ion pairs and dominate the cluster populations. Equilibrium constants obtained from molecular‐dynamics (MD) simulations show van't Hoff behavior with small transition enthalpies between the differently H‐bonded species. We show that cationic‐cluster formation prevents these ILs from crystallizing. With cooling, the (c–c) hydrogen bonds persist, resulting in supercooling and glass formation. Abstract : Doppeltes Plus : Festkörper‐NMR‐Spektroskopie unterscheidet Wasserstoffbrücken in konventionellen Ionenpaaren von denen zwischen Ionen gleicher Ladung in ionischen Flüssigkeiten. Die gemessenen Deuteron‐Quadrupol‐Kopplungskonstanten für beide Arten „doppelt ionischer Wasserstoffbrücken" unterscheiden sich deutlich. Die beobachteten kationischen Cluster verhindern, dass ionische Flüssigkeiten auskristallisieren und führen zu Unterkühlung und Glasbildung.